Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1089/ars.2007.1808
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis: Redox Mechanisms and Therapeutic Opportunities

Abstract: DESPITE ADVANCEMENTS IN THE treatment of critically ill patients, sepsis remains the leading cause of death in the ICU-an estimated 175,000 deaths per year (2). The incidence of sepsis in the United States ranges from 400,000 to 750,000 cases per year. Mortality due to sepsis is around 30% and increases with age from 10% in children to 40% in the elderly; mortality is 50% or greater in patients with the more severe syndrome, septic shock, and a recent study reported a 70% increase in the number of severe sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…During sepsis, many studies have shown that ROS and RNS may play a central pathogenic role. 8,9 Among ROS, HO…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During sepsis, many studies have shown that ROS and RNS may play a central pathogenic role. 8,9 Among ROS, HO…”
Section: Discussionmentioning
confidence: 99%
“…6 These reactive species represent a key element in the deleterious cascade process when endogenous antioxidant defences (for example, superoxide dismutase: SOD and catalase: CAT) 7 are overcome and/or when a redox imbalance occurs. 8,9 In sepsis several potential ROS sources, including mitochondrial electron transport and NADPH oxydase through macrophages and neutrophils activity, 7 are thought to be responsible for such an event leading to severe dysfunction and/or damage across multiple organs. 10 For example, NO generated within macrophages and other immune system cells, is implicated in pathologic vasodilatation resulting in hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…Small increases in one or the other can change intracellular signaling, causing changes in cellular actions. ROS and oxidative damage are known to been involved in the development of sepsis, and ROS are involved in the expression of cytokines as well (12). Clinical studies on treatment with antioxidants have by some authors been reported as promising (56), but due to conflicting results the clinical use of antioxidants has not yet been recommended by international sepsis guidelines (20).…”
Section: Stokes-einstein Radius (å)mentioning
confidence: 99%
“…Several studies have shown that ROS modulates TLR signaling (25,26). Because Nrf2 regulates several antioxidant defenses (see Table E1), we investigated inflammatory response in peritoneal macrophages isolated from LysM-Keap1 2/2 , LysMNrf2 2/2 , Keap1 f/f , and Nrf2 f/f toward different TLR ligands (TLR4-LPS, TLR3-Poly[I:C], TLR9-CpG, TLR2-LTA) and H 2 O 2 .…”
Section: Nrf2 Modulates Inflammatory Response By Redox Regulation Of mentioning
confidence: 99%